A PERIOPERATIVE AND PATHOLOGICAL COMPARISON OF THE IMPACT OF INTERVAL TO SURGERY FOLLOWING CHEMORADIATION FOR RECTAL CANCER. (8th June 2013) - McElvanna, K; Cole, A J; Spence, R; Moorehead, R J; Gilliland, R; McCallion, K; McAllister, I; Campbell, W J
Abstract : Introduction: The optimal interval between completion of neoadjuvant chemoradiation (NCRT) and resection for rectal carcinoma is unknown. Aims/Background: This retrospective study investigated the impact of interval to surgery on perioperative and pathological outcomes following NCRT for rectal cancer. Method: Patients with rectal carcinoma who underwent NCRT followed by rectal resection (September 2008–January 2013) were identified and divided into 2 groups according to their NCRT-surgery interval: Group A<9 weeks (n=36), Group B>9 weeks (n=44). Twelve complete clinical responders who were managed non-operatively were excluded. Demographic, perioperative morbidity, mortality, pathological and survival data were reviewed. Results: Eighty patients (42 male, median age 64.5 years) were included. Overall median interval to surgery was 9.4 weeks (range 5.3–23.6 weeks). Group A median interval was 7.1 weeks, Group B 12.6 weeks. Length of surgery, perioperative complication and mortality rates were not influenced by interval length. Median length of stay was increased with longer interval (A: 8 days v B: 10 days, p= 0.039). The overall complete pathological response rate was 18.8% (A: 27.8% v B: 11.4%). 2-year survival rates were similar (A: 83.3% v B: 89.9%) after a median overall follow-up of 35 months. Conclusion: A longer interval to surgery may be associated with an increased length of stay and in this cohort did not appear to confer a surgical or pathological benefit. A lower complete pathological response rate after a longer interval may be influenced by the selective non-operative management of complete clinical responders to NCRT.